2019
DOI: 10.3390/min9120780
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphic Age Comparison and Its Implications between the Zuoquan and Zanhuang Complexes in the Central North China Craton, Based on LA-ICP-MS Zircon U–Pb Dating

Abstract: The Trans-North China Orogen (TNCO) is well-known as an early Precambrian orogenic belt in the North China Craton (NCC). Three meaningful groups of metamorphic ages have been reported in the metamorphic complexes throughout the TNCO, including c. 1.85 Ga, c. 1.95 Ga, and c. 2.5 Ga. The spatial distributions and relationships of these ages provide notable insight into the formation timing and tectonic evolution of the NCC basement. The Zuoquan and Zanhuang complexes are exposed in the south–central TNCO and are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Widespread anatexis and intense reworking of the basement makes the formation ages difficult to extract. There is a paucity of previously reported ages of the Archaean rocks in the basement igneous complex, limited to a few metamorphic age reports of 2.51–2.46 Ga 27 , 28 , constraining that the basement formation predates this metamorphism. Our study constrains the anatectic event from monzogranite to be 2489 ± 6 Ma (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Widespread anatexis and intense reworking of the basement makes the formation ages difficult to extract. There is a paucity of previously reported ages of the Archaean rocks in the basement igneous complex, limited to a few metamorphic age reports of 2.51–2.46 Ga 27 , 28 , constraining that the basement formation predates this metamorphism. Our study constrains the anatectic event from monzogranite to be 2489 ± 6 Ma (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al (2016) reported an 1882 ± 15 Ma zircon U–Pb age for the Eastern Zanhuang domain diorite. Xiao & Chen (2019) reported ca. 1875–1858 Ma zircon U–Pb ages for metapelites of the central and southern of the Eastern Zanhuang domain, which are interpreted to be peak metamorphic ages.…”
Section: Discussionmentioning
confidence: 99%
“…Another Mid Neoproterozoic age ( 206 Pb/ 238 U 740 Ma and 207 Pb/ 235 U 685 Ma) was obtained in zircon (24) (spot AR2-7-R). This zircon's U (134.2 ppm), Th (289.8 ppm), and Th/U (2.16 ppm) are within the range limit of crustal magmatic zircons[5,6,19,23], and therefore show crystallization of a crustal magma, different to that of the Cryogenian metamorphic recrystallization zone (AR2-5R2) found in zircon(14). Consequently, the 740 to 685 Ma zircon could be an inherited grain.LateNeoproterozoic ( 206 Pb/ 238 U 544-616 Ma and 207 Pb/ 235 U 547-618 Ma) ages obtained in part of the studied zircons show that they registered Ediacaran events of three different periods (Early Ediacaran 605-617 Ma, Mid Ediacaran 571-579 Ma, and Late Ediacaran 498-554 Ma).…”
mentioning
confidence: 82%
“…Zircon geochronology is one of the key methods used to determine the ages of geological processes, including magmatic crystallization, different post-crystallization episodes [1][2][3][4][5][6][7], fingerprinted metamorphism [2,[8][9][10][11][12][13][14], and hydrothermal activity [15][16][17][18]. It also helps for provenance studies and paleogeographic reconstitution (e.g., [19][20][21][22][23][24][25][26][27][28][29]).…”
Section: Introductionmentioning
confidence: 99%